Do Business School Libraries Outsource? A Study of Gujarat State - Zala, Lavji N. (Journal of Information and Knowledge, 2017)
The study focuses on how business school libraries use “outsourcing” as a management tool to deliver good quality at low cost. It also examines the reasons, advantages and disadvantages behind outsourcing. To get the data about outsourcing of functions, services from business school libraries, a questionnaire was sent to 87 business school libraries in Gujarat (India). The findings indicate that many libraries use “Outsourcing” as an effective management tool and most libraries outsource their technical and computer related operations.